THE IN)DIRECTNESS OF TRANSLATIONS:: THROUGH THE SCANDINAVIAN WORKS PUBLISHED IN BRAZIL FROM 2017 TO 2021 - Almeida do Amaral, Regina; Torres, Marie-Hélène Catherine (Revista de Letras, 2025)
Several works of world literature, which circulated in Brazil for years through indirect translation, began to be retranslated directly, especially from the 2000s onward, which seems to reveal a trend of replacing indirect translation with direct translation or a preference for the latter over the former. This article aims to investigate whether this trend indeed exists, and to that end, a corpus of 50 Scandinavian literary works from the past thirty years, translated into Portuguese and published in Brazil between 2017 and 2021, will be analyzed. The (in)directness of the translations will be identified through a data collection process divided into three complementary stages: first, by analyzing the paratexts (Genette, 2009), specifically the morphological indices (Torres, 2014) of the translated books, which will also allow for determining how this (in)directness appears in the paratextual elements; second, by comparing information from the paratexts of the translated books with that of the primary source texts; and third, by searching for information about the translators' work to identify the language pairs they work with. By identifying the (in)directness of these works and comparing the proportion of direct and indirect translations within this small sample of publications, it will be possible to gain an understanding of the presence of indirect translation in the Brazilian publishing market, determine whether it has been decreasing or not and identify how it is presented. Keywords: (In)directness of translations. Paratext of translated books. Scandinavian literature.